Australia faces Southeast Asia : the emergence of a foreign policy - Vandenbosch, Amry, 1894-1990 (University of Kentucky Press, 1967)
Australia as a Western society in the Orient faces a unique and paradoxical challenge in her relations with her close but unfamiliar neighbors of Southeast Asia. Explicitly dependent upon British foreign policy until the fall of Singapore in 1942, Australia has reluctantly and painfully begun the task of developing a policy of her own. The Japanese conquest of Southeast Asia and many of the Pacific islands during the Second World War awakened Australia to the need to secure her own defenses and later, when Britain began a gradual withdrawal from Southeast Asia, Australia was thrown upon her own.